Απόκριση των οδηγών δικύκλών στα μηνύματα των πινακίδων μεταβλητών μηνυμάτων - Ιμπερσίμη, Εριόλα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Έργων Υποδομής και Αγροτικής Ανάπτυξης. Εργαστήριο Συγκοινωνιακής Τεχνικής, 2018)
This research aims at identifying the parameters that affect the response of powered two-wheelers (PTWs) to the messages of the Variable Message Signs (VMS). For this purpose, a questionnaire survey was conducted in the area of Athens. The questionnaire was designed using the stated preference method. Within the homework of the questionnaire a stated preference experiment was designed to estimate PTW response on VMS, under specific scenarios. The response was measured through the probability of the PTWs changing route in each of the explored scenarios. The scenarios were designed with the use of three parameters: incident type, incident impact and alternative route information provision. The survey took place in May and in the first two weeks of June 2017. 105 motorcyclists were randomly selected from 11 different regions of Attica while data were collected through face to face interviews. The results were analyzed through the discrete choice method which was used to design random probit models with random effects in order to take into account the heterogeneity among participants. Results showed that PTWs are mainly affected by the type of the occurred incident and the extent of the delays, while they do not seem to differentiate their response when receiving information about existing alternative routes. The response is greater when the incident is "Constructions", followed by «Accident» and finally «Congestion» which seems to affect them the least. In addition, riders who exhibit illegal driving behaviour (considering red light crossing, helmet use and non-permitted movement on roads) tend to be less affected by the VMS. Other factors such as gender, education, drivers' tendency to seek radio information about traffic conditions as well as perceived usefulness of VMS, play an important role in the response of the PTWs to the variable message signs. Similar results were also extracted from the analysis of subsets of the population.